PRINSIP KETERBUKAAN INFORMASI (DISCLOSURE) DALAM KEGIATAN PASAR MODAL MENURUT UU RI NO.8 TAHUN 1995 TENTANG PASAR MODAL: SUATU TINJAUAN YURIDIS - Anthon Nainggolan (Fakultas Hukum Universitas Kristen Indonesia, 2016)
Abstract Capital Market is a place to buy and sell or the stock exchanges, in general, the activity of capital market is held by the stock exchange institution, clearing institution, and other financial institutions whose activities are related to one another. One of the purpose of capital Market law is to guarantee that the activity of capital Market is done smoothly, proper and efficient and also to protect the importance or the interest of financiers and the public community. Transparancy is really needed in the activity of capital market, the meaning of transparency is (1) the nature of translucent light (2) real (3) clear or generally giving a smilar mean of transparent or visibility. Kata Kunci: Prinsip Keterbukaan Informasi